The Michael Eric Dyson reader / Michael Eric Dyson. - Dyson, Michael Eric (Basic Civitas, 2005)
This collection gathers the best of Dyson's growing body of work, which covers subjects as diverse as Michael Jackson, Derrida, Ralph Ellison, & the diplomacy of Colin Powell.